Ascorbate peroxidase modulation confirms key role in Leishmania infantum oxidative defence - Isabella Fernandes Martins Santos; Douglas de Souza Moreira; Karla Ferreira Costa; Juliana Martins Ribeiro; Silvane Maria Fonseca Murta; Ana Maria Murta Santi (Parasites & Vectors)
Abstract Background Ascorbate peroxidase (APX) has emerged as a promising target for chemotherapy because of its absence in humans and crucial role in the antioxidant defence of trypanosomatids. APXs, which are class I haeme-containing enzymes, reduces hydrogen peroxide using ascorbate to produce water and monodehydroascorbate, thereby preventing cell damage caused by H2O2. Methods We aimed to create an APX-knockout L. infantum line using CRISPR/Cas9. Despite unsuccessful attempts at full knockouts, we achieved deletion of chromosomal copies post-APX episomal insertion, yielding LiΔchrAPX::LbAPX parasites. We performed phenotypic characterization to assess the impact of these genetic modifications, which included the determination of APX transcript expression levels using quantitative PCR, drug sensitivity, infectivity, and parasite survival in macrophages. Results Quantitative polymerase chain reaction (PCR) analysis revealed a 10- to 13-fold reduction in APX transcript expression in LiΔchrAPX::LbAPX compared with wild-type (LiWT) and APX-overexpressing (Li::Cas9::LbAPX) parasites, respectively. The episomes in those knockdown parasites remained stable even after 20 drug-free passages in vitro. Li::Cas9::LbAPX parasites showed increased resistance to trivalent antimony (SbIII) and isoniazid, reduced tolerance to H2O2, and unchanged macrophage infectivity compared with LiWT. In contrast, LiΔchrAPX::LbAPX parasites were more sensitive to SbIII and isoniazid, exhibited greater susceptibility to H2O2-induced oxidative stress, and 72 h post-infection, showed fewer infected macrophages and intracellular amastigotes compared with LiWT parasites. Conclusions Our findings hint at the indispensability of APX in L. infantum and raise the possibility of its potential as a therapeutic target for leishmaniasis. Graphical Abstract